The Relationship Between Social Media Addiction And Personality Traits Among Adolescents - Iskajyan, Armine (ԱԵԳՄՄ հրատ.)
The article examines the relationship between adolescent social media addiction and personality traits. The research is highly relevant as social media is an integral part of modern people's daily lives. Although the Internet has numerous advantages, such as communication, information sharing, and access to educational resources, excessive use can lead to addiction. In this regard, teenagers are particularly vulnerable due to their developmental stage. A total of 165 teenagers aged 12-17 participated in the research. Tests and psychological interview methods were applied, and mathematical-statistical analysis was performed by calculating the Pearson linear correlation coefficient. The study found that social media addicts have higher levels of neuroticism and openness to experience than non-addicts. However, those with social media addiction had lower levels of extraversion, agreeableness, and conscientiousness than those without. Статья исследует взаимосвязь между зависимостью подростков от социальных сетей и их личностными чертами. Исследование является весьма актуальным, поскольку социальные сети стали неотъемлемой частью повседневной жизни современных людей. Несмотря на многочисленные преимущества интернета, такие, как коммуникация, обмен информацией и доступ к образовательным ресурсам, их чрезмерное использование может привести к зависимости. В этом контексте подростки особенно уязвимы из-за своих возрастных особенностей. Հոդվածն ուսումնասիրում է դեռահասների՝ սոցիալական ցանցերից կախվածության և անձային գծերի փոխհարաբերակցությունը: Հետազոտությունը խիստ արդիական է, քանի որ սոցիալական ցանցերը ժամանակակից մարդու առօրյա կյանքի անբաժան մասն են։ Թեև համացանցն ունի մի շարք առավելություններ, ինչպիսիք են՝ հեռահաղորդակցությունը, տեղեկատվության ստացումն ու տարածումը, կրթական ռեսուրսներին հասանելիությունը, սակայն համացանցի՝ չափից շատ կիրառումը կարող է հանգեցնել կախվածության ձևավորման։ Այս առումով հատկապես խոցելի են դեռահասները՝ պայմանավորված տարիքային առանձնահատկություններով։
Keywords: Հոգեբանություն